1996
DOI: 10.1093/infdis/173.3.684
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Glucan-Associated Enolase as a Main Cell Wall Protein of Candida albicans and an Indirect Target of Lipopeptide Antimycotics

Abstract: Growth-subinhibitory nonlytic doses of cilofungin (lipopeptide antibiotic affecting (1,3)-beta-D-glucan synthesis) inhibited the incorporation of 46- to 48-kDa glucan-associated (46K) protein into the growing cell wall of Candida albicans. The purified 46K protein constituent strongly reacted with a monoclonal antibody against enolase, a major cytoplasmic enzyme of the fungus. In addition, two internal fragments of 12- and 15-amino acid residues from a tryptic digest of 46K protein showed 100% identity with am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 42 publications
12
100
0
3
Order By: Relevance
“…is not exposed at the cell surface (3,51), and phosphoglycerate kinase has been detected at the cell surface of C. albicans cells and has also been detected to extend through the cell wall (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is not exposed at the cell surface (3,51), and phosphoglycerate kinase has been detected at the cell surface of C. albicans cells and has also been detected to extend through the cell wall (2).…”
Section: Resultsmentioning
confidence: 99%
“…These include enolase (55), a 47-kDa fragment of a 90-kDa heat shock protein (hsp90) (34,36), a 75-kDa heat shock protein, and a non-heat shock protein 96-kDa antigen (11), and some other glycolytic enzymes such as pyruvate kinase and alcohol dehydrogenase (52). Interestingly, some cytosolic proteins, such as enolase, members of the hsp70 family, and phosphoglycerate kinase, have been described to be bona fide components of C. albicans cell walls (2,3,31). Although some of these moieties have been used as potential marker antigens for antibody detection in invasive candidiasis (20,26,33,35,58), a simple, reliable, and easy-to-perform serological assay for the diagnosis of systemic Candida infections has not yet been developed.…”
mentioning
confidence: 99%
“…It has been described on the surface of neuronal, cancer and some haemopoietic cells as a novel plasminogen receptor [17][18][19] and has been implicated in the invasion of tissue by cells during metastasis [17][18][19]. It has also been described on the cell surface of Candida albicans as an abundant immunodominant antigen [20]. A study performed at the same time as this work has demonstrated that S. pneumoniae possesses the sequence for an AE-enolase and that the protein is expressed on the surface [21].…”
Section: Introductionmentioning
confidence: 99%
“…The lymphocytes from intravenously challenged mice responded to enolase as an immunodominant humoral antigen (Del Prete, 1992). Although the cytoplasmic location of enolase appeared to be established, enolase was detected by radioimmuno precipitation in cell wall extracts obtained after digestion of the wall -glucan network with -glucanase, zymolyase (Stec and Lebioda, 1990;Sundstrom and Aliaga, 1992;Angiolella et al, 1996). The release of enolase may be important in defining the selective stimulation of the host antifungal response during infection.…”
Section: Fungal Infection Of Vagina Is Sometimes Called a Thrush Canmentioning
confidence: 99%
“…It has been reported that in C. albicans and Candida tropicalis the cytosolic enzyme, enolase, was identified as an immuno-dominant antigen (Walsh et al, 199;Mitsutake et al, 1994;Angiolella, 1996). Candida enolase is a plasminogen-and plasmin-binding protein and the interaction of C. albicans enolase with the plasminogen system may contribute to invasion of the tissue barrier (Jong, 2003).…”
Section: Introductionmentioning
confidence: 99%